2020
DOI: 10.11648/j.ijepe.20200906.11
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the Wind Resource of Two Cities in the Sahara and Sahel in Chad

Abstract: The objective of this work is to map the wind resource of two cities of Ndjamena and Faya located respectively in Chadian Sahara and Sahel. As well as the evaluation of the annual energy produced at an altitude of 80m or 100m by the simulation of wind data from wind speed data collected from metrological stations in the Sahara and Sahel areas respectively in the cities of Ndjamena and Faya Airport, and available for five years. In this perspective, we start with the description of the site, the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Chad is full of solar potential with the annual hours of sunshine varying from 2850 hours in the South to 3750 hours in the North and the intensity of the global radiation varies on average between 4.5 to 6.5 kWh/m 2 /day, as shown in Figure 1 . The wind power is mainly found in the north of the country with speeds exceeding 5 m/s, as show in Figure 2 (Hassane et al, 2018;Didane et al, 2017;Mahamat Tahir et al, 2020;Mouangue et al, 2019).…”
Section: Study Areasmentioning
confidence: 97%
“…Chad is full of solar potential with the annual hours of sunshine varying from 2850 hours in the South to 3750 hours in the North and the intensity of the global radiation varies on average between 4.5 to 6.5 kWh/m 2 /day, as shown in Figure 1 . The wind power is mainly found in the north of the country with speeds exceeding 5 m/s, as show in Figure 2 (Hassane et al, 2018;Didane et al, 2017;Mahamat Tahir et al, 2020;Mouangue et al, 2019).…”
Section: Study Areasmentioning
confidence: 97%
“…Because of the rampant of desertification in Chad combined with widespread awareness, encourages the population and the government to opt for the development of renewable energies, solar and wind [1]. In 2008, faced with desertification which threatens the entire country, the Chadian government banned the use of firewood and charcoal, the main energy sources for Chadian households [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mahamat et al, in 2016 evaluated the wind resource in the city of N'djamena in Chad. They showed that the installation of a wind farm of 10 Vestas V80/1.8 MW turbines at 100 meters would produce 50,420 MWh of energy [11].…”
Section: Introductionmentioning
confidence: 99%